Portal Donasi Untuk Pembangunan Masjid Berbasis Web Menggunakan Framework Laravel - Yustria Mahendra Akbar; Rengga Asmara; Irma Wulandari (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2021)
This web-based donation portal application is online fundraising or donation application, especially for the construction of mosques. The purpose of this donation portal application is to be able to see the transparency of the mosque's financial statements by displaying the use of funds, the beginning balance, and also the ending balance. This application can view reports on the list of donors who have made mosque donation transactions in excel and pdf files and can also be accessed publicly. This application was developed using the laravel framework and MySQL database. In this application, there are 3 user roles, namely admin, fundraiser, and donor. This application has been tested at the Al-Affiyah Mosque in Malangsari Tanjunganom Nganjuk. The trial was carried out in three stages, among others: the donor user trial, the fundraising user, and finally the admin user trial. The result of this application is to provide convenience for fundraising and also donors to conduct web-based donation transactions as well as a means of reporting information on the use of mosque funds transparently.